2020
DOI: 10.1002/ece3.6986
|View full text |Cite
|
Sign up to set email alerts
|

Coupling between tolerance and resistance for two related Eimeria parasite species

Abstract: Host defense mechanisms evolve to alleviate the detrimental effect of parasites. They can be categorized into two components: resistance and tolerance (Råberg et al., 2009). Resistance is the ability of a host to reduce parasite burden, resulting from defense against parasite infection or proliferation early after infection (Schmid-Hempel, 2013). The negative effect of resistance on parasite fitness can lead to antagonistic coevolution. According to theoretical models, fluctuating host and parasite genotypes a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 58 publications
3
20
0
Order By: Relevance
“…To test whether the intensity of Eimeria DNA, oocyst counts or the combination of both are better predictors of host health, we used the maximally measured Eimeria DNA per gram of faeces and maximum OPG in a linear model trying to explain the weight maximally lost by an individual mouse (model A; LRT: χ 2 = 22.44, df = 3, P < 0.001). As expected [ 7 ], we found that both OPG and faecal Eimeria DNA explained maximum weight loss during infection (LRT: OPG: χ 2 = 6.66, df = 2, P = 0.036; genome copies per gram faeces: χ 2 = 18.18, df = 2, P < 0.001). The interaction between the two terms was found to be not significant (LRT: χ 2 = 2.54, df = 1, P = 0.11) (Table 1 ).…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…To test whether the intensity of Eimeria DNA, oocyst counts or the combination of both are better predictors of host health, we used the maximally measured Eimeria DNA per gram of faeces and maximum OPG in a linear model trying to explain the weight maximally lost by an individual mouse (model A; LRT: χ 2 = 22.44, df = 3, P < 0.001). As expected [ 7 ], we found that both OPG and faecal Eimeria DNA explained maximum weight loss during infection (LRT: OPG: χ 2 = 6.66, df = 2, P = 0.036; genome copies per gram faeces: χ 2 = 18.18, df = 2, P < 0.001). The interaction between the two terms was found to be not significant (LRT: χ 2 = 2.54, df = 1, P = 0.11) (Table 1 ).…”
Section: Resultssupporting
confidence: 88%
“…Twenty-two house mice ( M. musculus ) of the “wild-derived” inbred strains SCHUNT, STRA, BUSNA and PWD as well as F1 inter-strain crosses [ 7 , 23 – 25 ] were obtained from the Institute of Vertebrate Biology of the Czech Academy of Science in Studenec (licence: 61974/2017-MZE-17214). The age of the mice at infection ranged from 9 to 19.43 weeks and weight at start of experiments ranged from 15.16 to 28.95 g (Additional file 1 : Table S1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations